Effects of probiotic, prebiotic and synbiotic on growth performance, caecal bacterial populations and serum lipid concentrations of broilers - Saminathan, M.; Sieo, Chin Chin; Kalavathy, R.; Abdullah, Norhani; Ho, Yin Wan (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
A total of 360 one-day-old male broiler chicks were randomly assigned to four dietary treatments: basal diet (control) (T1), basal diet + 0.1% commercial probiotic (consisted of 11 probiotic Lactobacillus strains) (T2), basal diet + 1.0% prebiotic isomaltooligosaccharides (IMO) (T3), basal diet + 0.1% commercial probiotic + 1.0% prebiotic IMO (synbiotic) (T4). Body weights of chickens were measured at 1, 21 and 42 days of age. Feed intake and feed conversion was determined. At days 21 and 42, 18 chickens/treatment were euthanised and blood samples were collected for serum lipid analysis. Caecal contents were also collected from 6 euthanised chickens/treatment group and enumerated for lactobacilli, bifidobacteria, E. coli and total aerobes. The results showed that broiler chickens fed T2, T3 or T4 diet had significantly (P<0.05) higher body weight gain and better feed efficiency than those fed control diet (T1) at 1 to 42 days of age. The supplementation of probiotic, prebiotic and synbiotic also significantly (P<0.05) increased the caecal populations of lactobacilli and bifidobacteria and decreased the caecal E.coli and total aerobe populations. In addition, supplementation of T2, T3 or T4 diet significantly (P<0.05) lowered the serum total cholesterol, LDL cholesterol and triglycerides concentrations of broiler chickens at 42 days of age. The results indicated that prebiotic IMO (1.0%) and its symbiotic were effective in improving the performance of broiler chickens and in conferring other health benefits on the chickens.